The effects of virtual reality technology on negative emotions in the elderly: a meta-analysis - Liu, Miao; Zeng, Weisi; Liu, Surong (Frontiers in Psychology, 2025)
ObjectivesWe explored whether older individuals’ negative emotions were modified via virtual reality technology.MethodsWe conducted computer searches of four Chinese databases (CNKI, Wanfang, VIP, CBM) and four English databases (Embase, PubMed, Web of Science, Cochrane Library) from inception to February 12, 2025. Two researchers independently screened titles, abstracts, and full texts according to predefined inclusion and exclusion criteria, resolving discrepancies through discussion. The PRISMA 2020 flow diagram summarizes the study selection process. Meta-analysis was performed using RevMan 5.4 software.ResultsA total of 14 studies were included. The combined MD (95% CI) values and p-values were as follows: anxiety (SMD = −0.63; 95% CI: −0.82 to −0.45; P<0.05), depression (SMD = −0.49; 95% CI: −0.79 to −0.20; P<0.05), geriatric depression (WMD = −1.44; 95% CI: −2.57 to −0.31; P<0.05), and sleep quality (WMD = −1.94; 95% CI: −3.05 to −0.84; P<0.05). Fear of falling (WMD = −0.32; 95% CI: −2.81 to 2.16; p > 0.05) was not statistically significant, whereas the remaining outcomes all showed significant differences.ConclusionWhile virtual reality technology showed no significant effect on fear of falling, it appeared to improve depression, anxiety, and sleep quality in older adults. However, due to heterogeneity among studies, further high-quality studies are required to confirm these findings.Clinical trial registrationhttps://www.crd.york.ac.uk/prospero/display, ID=CRD42024623259.